Iron overload and non-alcoholic fatty liver disease - Datz, Christian; Müller, Elena; Aigner, Elmar (Minerva endocrinologica, 2017)
Approximately one third of patients with non-alcoholic fatty liver disease (NAFLD) show signs of disturbed iron homeostasis as indicated by elevated serum ferritin with normal or mildly elevated transferrin saturation. Mild hepatic iron deposition is the typical histological finding in these subjects and the term "dysmetabolic iron overload syndrome (DIOS)" is now used to describe this syndrome. From a clinical point of view, excess iron likely aggravates the natural course of NAFLD with regard to liver-related endpoints and extrahepatic disease complications although sound evidence is still lacking. The detrimental effect of iron is attributed to its capability to catalyse the formation of toxic hydroxyl radicals resulting in cellular damage. Conversely, reduction of body iron restores insulin sensitivity, and epidemiological evidence suggests that it delays the onset of complications such as T2DM, cardiovascular disease and also advanced liver disease. Iron accumulation in NAFLD is mainly due to inhibition of iron mobilisation from hepatocytes and Kupffer cells. Impaired iron export is related to inflammation and metabolic derangements that appear to impact on iron regulators, such as hepcidin, ferroportin and to a lesser degree on transferrin receptor, ferritin or copper. This review summarizes the current understanding of the role of iron in NAFLD.